TINJAUAN YURIDIS PELAKSANAAN PENGUJIAN PERUNDANG- UNDANGAN TERHADAP UNDANG-UNDANG DAN PERATURAN PEMERINTAH TENTANG RATIFIKASI ATAS KONVENSI INTERNASIONAL (STUDI KASUS RATIFIKASI KONVENSI INTERNASIONAL DI BIDANG HAKI). - Yoyon M. Darusman (KREATIF : Jurnal Ilmiah Prodi Manajemen Universitas Pamulang, 2013)
Rechstaats or The Rule of Law are the principles which confirmed as the based in operating of state and government of Republic Indonesia, refered to the Article 1 Sub Article 3 of the Constitutions of the Republic Indonesia of the Year 1945 (UUD 1945). In the historical and  law development of Indonesian law system, were not avoided that the effect of internal or external aspects could be changing the law products. Especially from the external factors such as global economic, international politic and international agreements. Its could be seen the progress and development of law system of Indonesia since the year 1945 till the year 1966 even untill the current year, were not created the stabilize law system.  To identify and formulize the problems, shall be determined ; so far the external factors can change the national law system, especially the law in the intellectual property rights(IPR), what is the constitions can keeping the national law product resulting the good law, especially the law in the intellectual property rights(IPR), and how the procedures to makesure that the constitutions can prevent the effect of external factors to the national law, especially law in the intellectual property rights(IPR).  And the results of the research concluded that ; The external factors such as the international convention and or international agreements, realy can changing the national law products, especially the law in the intellectual property rights(IPR). The Constitutions of Republic Indonesia (UUD 1945) has regulered how to prevent the effect of the external factors to the national law prducts, especially the law in the intellectual property rights(IPR). And Constitutions of Republic Indonesia (UUD 1945) has furnished the mechanism of judicial review to each international law products. especially the law in the intellectual property rights(IPR)